Review articleUltrastructural findings in pigs experimentally infected with bovine spongiform encephalopathy agent - Liberski, Pawel P.; Sikorska, Beata; Wells, Gerald A.H.; Hawkins, Steve A.C.; Dawson, Michael; Simmons, Marion M. (Folia Neuropathologica, 2012)
We report here an electron microscopic study of selected nervous system tissues from pigs infected experimentally with the agent of bovine spongiform encephalopathy (BSE). Generally, the ultrastructural neuropathology of BSE-affected pig brain resembled that of BSE-affected cattle brain. Spongiform change, in the form of membrane-bound vacuoles separated by septae into secondary chambers, dominated the pathology. Numerous astrocytic processes were visible in close conjunction with elongated microglial cells. Neuronal degeneration presented as either dystrophic neurites or by the formation of autophagic vacuoles. Altered subcellular organelles: mitochondria, electron-dense bodies, autophagic vacuoles, neurofilaments and “branching-cisterns” accumulated in abnormal neurites. Autophagic vacuoles appeared as neuronal cytoplasm of increased electron-density sequestrated by intracytoplasmic membranes. Tubulovesicular structures were numerous, particularly in the cerebellum. Unusual crystalloids were observed in the white matter. In conclusion, experimental BSE in pigs demonstrated ultrastructural pathology in keeping with that observed in other spongiform encephalopathies.